Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Review - Page 470: 130



Work Step by Step

Using $i=\sqrt{-1}$ and the properties of radicals, the expression $ \sqrt{-2}\cdot\sqrt{-5} $ simplifies to \begin{array}{l} \sqrt{2}\cdot\sqrt{-1}\cdot\sqrt{5}\cdot\sqrt{-1} \\= (i\sqrt{2})(i\sqrt{5}) \\= i^2\sqrt{10} \\= (-1)\sqrt{10} \\= -\sqrt{10} .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.